ANALISIS PEMELIHARAAN SUCTION PUMP DI RSUP HAJI ADAM MALIK MEDAN - Primasyukra, Mhd. Aldi; Sinulaki, Yogi Alfares (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Checking the accuracy of the required medical equipment on the suction pump calibrator with measurements that have been made using a standardized pressure gauge. The purpose of this study was to determine the maintenance of the suction pump at Haji Adam Malik Hospital Medan in 2022. The method used in this study was descriptive qualitative. The tool used is a suction pump and a questionnaire as a measuring tool used. The results showed that the motor rotation function, cable resistance, and hose were not in accordance with the suction pump maintenance standard, and encountered problems, namely the tool could not work as usual, so that maintenance repairs were carried out on the tool, namely readjusting the value according to the standard on the suction pump tool, so that the tool was able to work well.